Some notes on politics in western Córdoba between the 19th and 20th centuries. The case of the priest José Gabriel Brochero - Ayrolo, Valentina; Ferrari, Marcela (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2005)
Political intermediaries are usually individuals with little notoriety at the national level. However, at the regional or local level, they are essential to build consensus and provide electoral support for the candidates proposed by the parties. This assertion becomes even more valid in highly personalized political contexts, such as the late oligarchic regime and the beginning of democratic expansion in Argentina. Intermediaries acted as hinges between the first-line political casts and the population, influencing specific geographic spaces. They did not necessarily respond to a single party nor were they caudillos. They could place their influence at the disposal of different political forces, according to the interests they permanently or occasionally pursued. Behind them, they could drag along a potential electoral flow to negotiate with the men in power. The practices they put in place to gain support, "downwards", and trust, "upwards", were very varied. This type of intermediary combined rational and progressive speeches in the political or economic spheres, good intentions, exchanges of favors, promises, etc.... The micro-analytical observation reveals these aspects used by these political "connectors" which contributed to put into operation the action of power. In this article we try to elucidate some of these aspects through a case study: that of the priest José Gabriel Brochero. We consider this character to be particularly interesting because, without being a caudillo or a career politician, he shows the way in which an ego that is not a member of the stable political staff can enter politics in pursuit of an objective: the material and social progress of his area of influence. Through the analysis of his correspondence, we will observe how he made his relational capital in the region available to the politicians of the day, maximizing the benefits to be obtained from a reduced but significant nucleus of personal contacts. The paper includes a very brief description of the characteristics of the region and a biographical presentation of the central political actor, which are essential to introduce the intermediation practices of a second or third order political actor.